Disease Severity of Geminivirus Infection on the Chili Plants at Baki, Sukoharjo - Annisa Dewi Setyowati; Suranto Suranto; Supyani Supyani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
Geminivirus a virus family commonly infecting vegetable crops such as chili peppers (Capsicum annuum L.). The initial symptoms for the infections are bleaching, vein clearing, leaves thickening, cupping, leaves mosaics, and leaves malformations. This virus infection has been reported to cause serious disease and yield losses. This research was aimed to know the disease severity of the infected chili plants in three plantations in Sukoharjo. A direct survey was used as the research method. The result showed the disease severity has reached a high level. The percentage of disease severity was 90.64% in the first location, 93.01% in the second location, and 71.99% in the third location.